Control interno al area administrativa del Colegió mixto particular “Carlos Lozada Quintana” del Cantón La Maná, periodo. 2014. - Herrera Pérez, Consuelo de Lourdes (2015)
The Internal Control in private educational institutions is to evaluate the functions and procedures in administrative performance and results of the activities that have been assigned to officials to verify whether these have been executed correct and efficient manner. It is also used as an element of self control that allows an accurate, timely and systematic diagnosis of the entity as a whole. This research work aims to assess the administrative area has the College for the purpose of determining the level of risk and trust in the process of roles, it was achieved through the evaluation of internal control that was subject to College and through this to inform those who are part of the Site, which are explained and disclosed the results of the administration to citizens…..